CT guided lung biopsy complications: a single centre prospective study - Mir, Mohd Farooq; Naik, Muzafar Ahmed; Malik, Javid Ahmed (International Journal of Research in Medical Sciences, 2018)
Background: Computed tomography (CT) guided percutaneous transthoracic needle biopsy of lung is a routine procedure in patients with suspected malignant lung lesions which are either peripheral or not amenable to biopsy on fibreoptic bronchoscopy. Methods: This prospective study was conducted to obtain complication rates based on patient and physician experience after CT guided lung biopsy of central and peripheral lung lesions. Results: In our study 96 patients were included with 78 patients with peripheral and 18 patients having central lung lesions. The reported post procedural complication rates of CT guided lung biopsy were pulmonary haemorrhage 33.3 %, pneumothorax 21.9%, haemoptysis 15.6%, cough 6.3%, haemothorax 3.1% and fever 3.1%. Two patients required inter costal tube drainage. There was no reported mortality of CT guided lung biopsy in our centre. Conclusions: Pulmonary haemorrhage and pneumothorax are the most common complications of percutaneous transthoracic needle biopsy of the lung, the former one is common with central and the latter one with peripheral lung lesions.